Development of a basketball game concept for 5th grader 3rd elementary school Margomulyo - sceisarriya, vega mareta (PHEDHERAL, 2023)
Movement learning in physical education is divided into cognitive stages, associative stages, and automatic stages. The cognitive stage is the main capital in learning student motion to understand the concept of motion we want. The concept map in this basketball game aims to supplement teaching materials for student basketball games. This study uses a descriptive-quantitative design referring to the Lee Owens development model. The research data is the result of expert validation, small group trials, and large group trials. In the results of the small group trial, a percentage of 82% was obtained, meaning that concept maps could be used. In the large group trial, a percentage result of 84.1% was obtained, meaning that the basketball game concept map was declared fit for use. The suggestions in developing this concept map are that it is hoped that this research will go in a further direction as follows: (1) The research subjects are broader and more in-depth (2) The research is not only carried out at the elementary school level, class V, but all upper classes with big ball learning especially basketball.